Slim cigarette smoking prevalence among Canadian youth smokers: Implications for federal standardized packaging legislation - Minaker, Leia M. (Can J Public Health, 2017)
OBJECTIVES: Tobacco companies market to females and young people through slim cigarette design features and packaging. This study assessed the prevalence and perceptions of slim cigarette smoking in grades 9–12 student smokers across Canada using multiple data sources. METHODS: Data from three cycles of the Youth Smoking Survey (2008/2009 to 2012/2013) and one cycle of the Cancer Risk Assessment in Youth Survey (2015) were used. The prevalence and perceptions of slim cigarette smoking among current smokers were compared by sex and grade. RESULTS: In all surveys, the rate of slim cigarette use was higher among females than males; however, this difference was not statistically significant. In the two most recent surveys, grades 9–10 students had a significantly higher prevalence of use compared with grades 11–12 students. The majority of students (59.8% of females and 53.3% of males) responded, “I don’t know” to the survey item seeking to determine perceptions of harm of slim cigarettes compared with regular cigarettes. CONCLUSION: Slim cigarette use among Canadian grades 9–12 students represents a small but growing problem. Youths’ uncertainty around the harms associated with slim cigarette use and the effect of slim cigarette packaging and design on harm perceptions indicate the need for product design regulations and further education in Canada.